The effect of different water aerobics intensities on anthropometrics and muscle strength - Fail, L. B.; Marinho, D. A.; Neves, P. P.; Marques, M. C.; Pereira, R.; Neiva, H. P. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION The literature demonstrates there is not enough information to indicate the intensity at which some aquatic activities should be performed to obtain the intended results (Faíl et al., 2022). Therefore, it becomes essential to further understand the impact of different intensities that can be used in aquatic activities. Thus, this study aimed to verify the effects of 12 weeks of water aerobics carried out at two different intensities in anthropometrical and muscle strength variables. [...]